Local Value Based Education Management: A Strategy for Strengthening Student Character to Face the Global Era - Ahmad Qurtubi (PT. Anagata Sembagi Education, 2024)
Local value-based education management is a relevant strategy in strengthening student character amid the challenges of the globalization era. This study aims to analyze the concept, implementation, and impact of applying local values in education management as an effort to form a generation with character that is adaptive to global changes without losing cultural identity. The research method uses a qualitative approach with data collection techniques through literature studies, interviews, and observations. The results show that the integration of local values, such as gotong royong, cultural wisdom, and traditional ethics, into the curriculum and learning activities can shape students' characters who are resilient, have integrity, and have critical thinking skills. This strategy also helps students recognize and appreciate their cultural identity in the midst of globalization. Thus, local value-based education management is an innovative solution to face the challenges of the global era while maintaining the nation's cultural heritage. Strengthening Student Character, The integration of local values in education contributes significantly to the formation of student character that is resilient, integrity, and critical. Students are not only equipped with academic knowledge but also values rooted in local culture, such as gotong royong, traditional ethics, and local wisdom, so that they are able to face global challenges with a wise attitude.